Strategies of Internet CafÃ© Owners in Preventing Motorcycle Theft (A Case Study of Internet CafÃ© X in Tualang District) - M. Hardi Mustafa; Askarial A (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
In this modern era, the free and easy traffic of sophisticated information has increasingly made it easier for most people in this country to know? Lear what is happening in all corners of this diverse earth. From this process, many people take advantage of advances in information for business purposes. Businesses providing information services or internet cafes that are currently developing target consumers from visus social strata and all ages, both children and the elderly. Users can access information freely without any filters carried out by internet cafe business providers. This makes information users more free to do what they want for reasons of freedom of information without considering the negative effects. This type of research is descriptive qualitative using qualitative methods. namely descriptive research. The most practical way to do this is to do an in-depth interview (in-depth interview). in-depth interviews are the process of obtaining information for research purposes by means of face-to-face questions and answers between the interviewer and the informant or interviewee, with or without using an interview guide. In this research, the author made key informants and informants the research object. Because by conducting interviews with key informants and informants to get answers from the research results, the internet cafe owner's strategy for preventing motorcycle theft is by providing outreach such as putting up banners and telling internet cafe customers directly to guard and double lock their vehicles. The police have also implemented measures to prevent motorbike theft from occurring. Namely by prevention through primary, secondary and tertiary actions. Actions are carried out by providing socialization and views of crime to community members,